BIOANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR ESTIMATION OF TIZANIDINE IN K2EDTA HUMAN PLASMA BY USING LC-MS/MS - Bhadauria, Dr. R.S.; Joshi, Dr. D.B. (Journal of Biomedical and Pharmaceutical Research, 2019)
Bioanalytical method Validation employed for quantitative determination of drug and their metabolites in biological fluids. Comprises all criteria determining data quality, such as selectivity, accuracy, precision, recovery and senstivity. The main purpose of method validation is to demonstrate that a specific Bioanalytical method can reliably determine the concentration of drug in study sample with high degre of confidence. Validation does not means that method is perfect, but validation means method has met a set of criteria to ensure that it is reliable and consistent. Tizanidine is a central alpha 2 adrenergic agonist –inhibits release of excitatory amino acid in the spinal interneurones. It may facilitate the inhibitory transmitter glycine as well. It inhibits polysyneptic reflexes reduce muscle tone and frequency of muscle spasms without reducing muscle strength. Following oral administration, tizanidine is essentially completely absorbed .The absolute oral bioavailability of tizanidine is approximately 40%, due to extensive first-pass hepatic metabolism. Tizanidine is extensively distributed throughout the body with a mean steady state volume of distribution of 2.4 L/kg following intravenous administration in healthy adult volunteers .tizanidine is approximately 30% bound to plasma proteins. Keywords: Bioanalytical method Validation, LC-MS/MS, Human Plasma, Tizanidine, HPLC.